Influence of poor Non Motorized Transport (NMT) Infrastructure leading towards declination in NMT users (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of this study is to redefine or suggesting the infrastructure for Non Motorized Transport (NMT) at congested intersection in Nagpur City, four congested intersection where selected for the study which is having high NMT contribution along with the Motorized Transport. The highest priority should go to the public transport, walking and non motorized vehicles that are accessible to almost everyone and have low impact. Developing countries with the advancement in automobile sectors it has been observed from the last past year's that the countries are getting dominated for using motorized vehicles as their major mode of transportation and avoiding the use of public transportation. Due to continuously increase in motorized transport environment witness adverse effects, increasing green house gases, sudden climate change and contributing towards pollution. It has been observed that due to inadequate non motorized infrastructure people or user tends to use motorized transportation. However often developing countries face challenge in the form of lack of pedestrian Infrastructure, nonexistent sidewalk, inadequate cycling Infrastructure. In terms of infrastructure, what differentiate advance cities are not highway or subway but quality of sidewalk and cycle ways. Traffic volume study is carried out at selected location by manual count method to determine the Level of Service (LOS) by Highway Capacity Manual (HCM 2010).The motive of this study is to encourage the public to use the non motorized transportation and to review the impact of poor non motorized transport (NMT) infrastructure results into increased Motorized vehicle.